(untitled) - Edelman, Murray (Cambridge, UK, 2001)
This book is an examination of how concentrations of social and economic power result in public languages of politics that are necessarily image-based, vague, and misleading in their denial of undemocratic tendencies. As a result, public discourses of democracy tend to be populistic, emotional, and likely to emphasize images of progress rather than structural inequalities in their formulations of public problems
Keywords: Truyền thông chính trị,Thuật phát ngôn,Communication in politics,Communication,Rhetoric; Khía cạnh chính trị,Political aspects,Political aspects